Comparative Analysis of Entrepreneurial Innovation Factors in 25 National States - Lungu, Anca-Elena (ANDULI, Revista Andaluza de Ciencias Sociales, 2022)
At the base of entrepreneurship lies the challenge that individuals with entrepreneurial skills (entrepreneurs) must accept at the outset in an increasingly dynamic environment dominated by uncertainty. Innovation and the innovative process have to be constant in entrepreneurial actions. Building on this hypothesis, one cannot ignore the essentiality of the entrepreneur’s adaptability to market requirements and demands. The assumption of risks and uncertainty evidently generates a motivation at an individual level in entrepreneur-actors. Action in a dynamic environment leads to the urgent necessity of adopting new technologies in business. From the perspective of implementing and using innovation, this study uses quantitative methods to illustrate the challenges related to innovation in the business environment. Our sample comprises 25 national states, selected according to their rank on the Global Entrepreneurship Index. Taking as a starting point the influence exerted by innovation and the innovative process within companies, we identify certain elements that justify the development level of entrepreneurship. Using Principal Component Analysis, we confirm that innovation, in its various forms (process, product, etc.); can significantly affect discrepancies among the countries. The three factorial axes resulting from the analysis of the main components (competition, product innovation and process innovation) explain the positioning of States on either side of the international hierarchy.